Effect of vacuum negative pressure aerobic hydrolysis pretreatment on corn stover anaerobic fermentation - Xu, Yonghua; Song, Yunong; Jiang, Hao; Zhang, Hongqiong; Sun, Yong (International Journal of Agricultural and Biological Engineering, 2023)
Lignin degradation restricts corn stover anaerobic fermentation efficiency. The vacuum negative pressure aerobic hydrolysis pretreatment of corn stover was tested, and the optimal combined pretreatment conditions were presented in this paper. Because of the physical characteristics of light weight and large specific porosity of stover, it led to the formation of a scum layer during the fermentation process and thus reduced the gas production rate. In the pretreatment design, the vacuum conditions (0.02-0.08 MPa) and dwell time (5-20 min) were selected to see the changes of volumetric weight, swelling and specific porosity of corn stover, resulting in an increase of the volumetric weight by 7.18%-28.72%, increase of the swelling by 3.18%-58.59%, and decrease of the specific porosity by 9.34%-38.59%, as compared with the CK group. Continuous vacuum negative pressure treatment could discharge the air inside the stover destroy the microstructure, and cause the stover to settle more easily during the aerobic hydrolysis process. The optimal aerobic hydrolysis temperature and time were determined to be 39℃ and 12.65 h, respectively. With the optimal pretreatment, the corn stover anaerobic fermentation test realized the cumulative methane yield as 260.44 Ml/g·VS, 22.71% higher than that of CK group; meanwhile, the hydraulic retention time was shortened by 32.39%.Keywords: corn stover, vacuum, negative pressure, pretreatment, aerobic hydrolysis, anaerobic fermentationDOI: 10.25165/j.ijabe.20231602.7975Citation: Xu Y H, Song Y N, Jiang H, Zhang H Q, Sun Y. Effect of vacuum negative pressure aerobic hydrolysis pretreatment on corn stover anaerobic fermentation. Int J Agric & Biol Eng, 2023; 16(2): 241–248.